THE RULE OF BRAND ELEMENT AND SERVICE QUALITY ON CUSTOMER SATISFACTION IN MOBILE GAMING: A STUDY OF POKÉMON GO PLAYER IN MALANG SOCIETY - IMRAN, MUHAMMAD FADLI (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
This research is aim to examine the impact Brand Image, Brand Experience, Service Quality, and Perceived Value on Customer Satisfaction. The population of this research is the player of Pokémon GO in Malang City. This research used quantitative approach with questionnaire to collect data. There are 150 questionnaire distributed to every customers who already playing Pokémon GO in Malang. The gathered data is analyzed by using quantitative methods i.e., multiple regression analysis based on application named SPSS version 17.00. The results of this research show that there is a positive influence together with simultaneous and partial effect between brand image, brand experience, service quality, and perceived value on customer satisfaction. While service quality is the most dominant variable that affects customer satisfaction.Keywords: Brand Image, Brand Experience, Service Quality, Perceived Value, Customer Satisfaction